Biomarkers in management of inflammatory bowel disease - Moniuszko, Andrzej; Wiśniewska, Anna; Rydzewska, Grażyna (Gastroenterology Review/Przegląd Gastroenterologiczny, 2013)
In recent years the use of faecal and serologic biomarkers has been evaluated in the diagnosis and management of inflammatory bowel disease (IBD). Faecal calprotectin (FC) has been proposed as a surrogate marker for intestinal inflammation; elevated concentrations in IBD patients have been confirmed in numerous studies. Already available rapid calprotectin tests help to differentiate between IBD and irritable bowel syndrome. Faecal calprotectin greatly correlates with endoscopic activity scales and reflects the mucosal healing; thus in patients in clinical remission high levels of it correlate with increased risk of disease relapse in the following 12 months. Adapting the calprotectin assay as a screening test before colonoscopy enables a significant reduction in endoscopic procedures. ANCA/ASCA antibodies have been used in IBD diagnosis and to distinguish CD from ulcerative colitis (UC). Lactoferrin and S100A12 protein were also used to assess the disease activity. This review aims to present the actual potential of biomarker assays for faster diagnosis of IBD and their ability to monitor the disease course, predict exacerbations and improve the way IBD is managed.